2018
DOI: 10.1007/s00520-018-4250-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ferric carboxymaltose on the evolution of hemoglobin and ECOG performance status in iron-deficient patients with solid tumors: a 3-month follow-up retrospective study

Abstract: Even though there was no improvement in ECOG index, this study did identify an increase of Hb for patients receiving FCM, indicating its potential benefit in iron-deficient cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…In agreement with Steinmetz et al, this trial suggested baseline ferritin levels <100 ng/mL as the predictor of response. Treatment with FCM has also been associated with a significant increase of QoL in patients with various solid tumors [82].…”
Section: Evidence For Iron Treatment In Cancer Anemiamentioning
confidence: 99%
“…In agreement with Steinmetz et al, this trial suggested baseline ferritin levels <100 ng/mL as the predictor of response. Treatment with FCM has also been associated with a significant increase of QoL in patients with various solid tumors [82].…”
Section: Evidence For Iron Treatment In Cancer Anemiamentioning
confidence: 99%
“…In comparison, among the three largest reported series of patients with cancer who received FCM, baseline iron saturation and ferritin levels were only available in 54% to 74% and 54% to 57% of patients, respectively. 7,8,11 Excluding patients who died or received transfusions, all of our patients underwent assessment of haemoglobin levels at the pre-specified intervals in the first 4 weeks. The relative completeness of the data enhanced the study's statistical precision.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, previous studies in patients with cancer focused on anaemia with baseline haemoglobin levels of 9 to 11 g/dL. [7][8][9][10][11][12] In addition, the majority of the aforementioned studies assessed the trend of haemoglobin levels at a monthly interval and therefore did not provide much information about haemoglobin levels during the first 4 weeks after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…К настоящему времени поступает все больше доказательств эффективности монотерапии в/в препаратами железа, особенно при использовании более новых соединений третьего поколения [47,48]. Первоначально в трех небольших исследованиях с участием пациенток онкогинекологического профиля, которые получали химиолучевую терапию, зарегистрировано значительное снижение потребности в гемотрансфузиях после применения в/в препарата железа сахарозы [49][50][51].…”
unclassified